Glutamate Release through Volume-Activated Channels during Spreading Depression - Basarsky, Trent A. (J Neurosci, 1999)
Volume-sensitive organic anion channels (VSOACs) in astrocytes are activated by cell swelling and are permeable to organic anions, such as glutamate and taurine. We have examined the release of glutamate through VSOACs during the propagation of spreading depression (SD). SD was induced by bath application of ouabain in hippocampal brain slices and was monitored by imaging intrinsic optical signals, a technique that provides a measure of cellular swelling. The onset of SD was associated with increased light transmittance, confirming previous studies that cellular swelling occurs during SD. NMDA receptor antagonists, either noncompetitive (MK-801, 10–50 μm) or competitive (CGS-17355, 100 μm), reduced the rate of propagation of SD, indicating that glutamate release contributes to SD onset. SD still occurred in zero Ca(2+)–EGTA (0-Ca(2+)–EGTA) solution, a manipulation that depresses synaptic transmission. HPLC measurements indicated that, even in this solution, there was significant glutamate release. Two lines of experiments indicated that glutamate was released through VSOACs during SD. First, 5-nitro-2-(3-phenylpropylamino) benzoic acid (NPPB), a blocker of VSOACs, depressed the rate of propagation of SD in a manner similar to NMDA antagonists. Second, NPPB inhibited the release of glutamate during SD in 0-Ca(2+)–EGTA external solution. These results indicate that cellular swelling during SD causes the activation of VSOACs and the release of glutamate by permeation through this channel. Cellular swelling is a result of neuronal activity and is observed during excitotoxicity. Therefore, glutamate release from VSOAC activation could occur under conditions of cell swelling and contribute to excitotoxic damage.